Panduan Pelesarian Bangunan Tua di Kawasan Pecinan Pasar Baru Bandung - Nurmala, . (Center for Research and Community Services ITB, 2003)
Preservation of old buildings in Bandung Chinatown-Pasarbaru still faces many problems. One of the problems is the lack of preservation guidelines, so that is destruction, rehabilitation and development of old/historic building occurs without respecting the characters of the buildings. The substance of preservation guidelines is identified by studying the concepts and by identifying the technical problems on old building preservation in the observation area. These preservation concepts consist of coverage, criterions, process, preservation activities, issues of concern, scope of issues and element that would be controlled. The technical problems consist of old and historic building character in the observation area. These character are classified based on each typology. This study also formulates the component and element of the building that would be controlled based on preservation aspect in the guidelines and design approach from the literature. The guidelines consist of rules and recommendations for old building elements and component which are translated from the preservation principle.Keywords: old buildings, preservation guidelines, rules, recommendation